Evolved individual differences: Advancing a condition-dependent model of personality. (October 2015) - Lewis, David M.G.
Highlights: Personality taxonomies do not explain the origins or structure of personality. Condition-dependent evolutionary models may help fill this explanatory gap. Conditional mechanisms' outputs depend on the benefits of alternative trait levels. I advance novel hypotheses about trait variation and covariation. I conclude with future research directions for explaining personality differences. Abstract: The field of personality psychology offers a wealth of robust empirical research and a successful descriptive taxonomy, but neither explains the origins of the structure of human personality nor elaborates a generative framework for predicting the specific conditions that evoke the development of distinct personality traits. Exploration of traditional personality constructs within an evolutionary adaptive individual differences framework may help fill this explanatory gap. Personality traits exhibit functional features and patterns of variation expected from psychological adaptations designed to solve survival- and reproduction-related challenges recurrently faced during our species' evolutionary history. Condition-dependent evolutionary models of personality have been proposed for decades, but only recently have begun to see empirical investigation. These models posit that species-typical psychological mechanisms take as input cues from the individual's phenotype that would have been ancestrally linked to differential cost–benefit tradeoffs of alternative personality strategies, and produce as output personality trait levels with the greatest probabilistic net benefit for the individual. This paper elaborates a more nuanced conceptual framework that builds on earlier conceptualizations of condition-dependent traits to yield new and untested hypotheses about personality trait variation and covariation. It then describes clear future research directions for empirically investigating these readily testable hypotheses.